The Italian Law Enforcement System Used to Protect Cultural Properties, With Particular Reference to Databases and Mass Media - Lukács, Dalma (Kriminalističke teme, 2018)
The basic pillar of the protection of cultural goods is the database which I present in this paper. Leonardo and iTPC can be considered as the next-generation database of stolen cultural properties, what the international law enforcement agencies do not have. During the the research, I have used the methods of interviews and the experiences gained during my study trip in Italy. Modern technology, and through this, mass media is essential to enhance the protection of cultural properties.